Strengthening the Constitutional Court’s Authority to Adjudicate on Disputes Regarding the Result of Regional Head Election In Indonesia: an Urgency to Clarify the Constitutional Framework - Hidayat, Rayhan Naufaldi; Novrizal, Mohammad - (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Since the Constitutional Court is the guardian of democracy and the constitution, it is responsible for ensuring that elections in Indonesia are held in a democratic manner. The power rotation process must be carried out calmly and collectedly, without any significant breaches of people's fundamental rights or acts of violence. The instrument of authority is a necessary component for the Constitutional Court to achieve all of the goals stated in the text. The functioning of the Constitutional Court's authority to resolve disputes relating to the outcomes of Indonesia's regional head elections will be further examined in this research. Then, in order to determine the necessary treatments, a worldwide comparison of the increasing symptoms with those of other countries will be carried out. The research methodology used is doctrinal legal study using a comparative constitutional research strategy. The findings demonstrated the weakness of the Constitutional Court's authority to resolve disputes over the outcomes of regional head elections. It was observed that there were three distinct interpretations of the norms that formed the basis for legitimacy, which resulted in progressive changes to this authority. The Republic of Indonesia's 1945 Constitution's ambiguous normative framework for regional head elections has led to ongoing interpretations It is really unique in light of the fact that the constitutions of 43 of 72 unitary nations in the world fully regulate election procedures and the course of dispute settlement in the event of a dispute. In fact, they specifically mention in one or more of the Constitutional Court's complete authority articles the nature of authority and the scope of elections. It is imperative to promptly establish the precedent with clear legal politics declaring that regional head elections are elections in order to guarantee that the Constitutional Court hears the majority of cases.